In situ formation of chemically integrated and mechanically interlocked interphases enables robust epoxy-copper adhesion - Ting Xin; Zeyu Zheng; Zuo Li; Yue Wu; Yang Liu; Binbin Zhou; Jibao Lu; Xiaoliang Zeng; Fan Yang; Gang Li; Rong Sun; Pengli Zhu (Chemical Engineering Journal, 2026)

Callosobruchus maculatus feeding triggers multilevel defenses in cowpea seeds: from germination regulation to defensive metabolite biosynthesis - Hainuo Hong; Ming Zhang; Jiamei Geng; Qiulin Chen; Zheyi Shi; Yang Gao; Ying Zhou; Zeng‑Rong Zhu (Journal of Pest Science, 2026)

Correction to: Life Cycle and Circadian Rhythms in Central Resident Immunity and Neuropsychiatric Pathology - Zhixin Lim; Ha Linh Nguyen; Yuanyuan Zeng; Qingyue Qu; Yan Le; Ming Sun; Xiaoyu Wang; Hong Zhu; Yuchen Qian; Saboor Saeed; Huaizhi Wang; Dazhong Rong; et al. (Neuroscience Bulletin, 2026)

Life Cycle and Circadian Rhythms in Central Resident Immunity and Neuropsychiatric Pathology - Zhixin Lim; Ha Linh Nguyen; Yuanyuan Zeng; Qigngyue Qu; Yan Le; Ming Sun; Xiaoyu Wang; Hong Zhu; Yuchen Qian; Saboor Saeed; Huaizhi Wang; Dazhong Rong; et al. (Neuroscience Bulletin, 2026)

Differential analysis of lipid profiles in natural Calculus Bovis and Bovis Calculus Sativus by UHPLC-MS/MS - Qiang Mao; Huan Zhong; Wan-Li Liang; Jin Dai; Rui-Ting Huang; Yi-Di Wang; Di-Yang Sun; Kai Tang; Long-Fei Xia; Hai-Biao Gong; Yi-Fang Li; Wan-Yang Sun; et al. (Journal of Natural Medicines, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Boosting sulfamethoxazole degradation via peroxymonosulfate activation: Critical comparison of intrinsic and external nitrogen-doped biochar modulated by pore former - Zijun Zeng; Sen Wang; Anthony Umeh; Gopalan Anantha Iyengar; Houfan Wu; Hongwei Rong; Runliang Zhu; Yunfei Xi; Ravi Naidu (Journal of Hazardous Materials, 2026)

Host switching and successive subculturing drive adaptive responses in Liriomyza sativae - Yang Gao; Wei He; Ming Zhang; Hai-Nuo Hong; Jin Wang; Ying Zhou; Zeng‑Rong Zhu (Journal of Pest Science, 2026)

Thioredoxin PgTRX acts as a protein elicitor to suppress green mold in citrus fruit via modulation of glutathione metabolism - Rong Zhu; Ou Chen; Yao Xu; Rui Huang; Wenjun Wang; Jian Ming; Kaifang Zeng (Postharvest Biology and Technology, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Cataract Aggravates Alzheimer-Like Pathologies and Cognitive Deficits in an APP/PS1 Mouse Model - Zhao Geng; Zhong-Yuan Yu; Jun Tan; Xuan-Yue Wang; Gui-Hua Zeng; Jiang-Hui Li; Yu-Di Bai; Xiao-Qin Zeng; Yu-Peng Zhu; Cheng-Rong Tan; An-Yu Shi; Yu-Hui Liu; et al. (Neuroscience Bulletin, 2026)
Clinical investigations have suggested a potential link between cataracts and Alzheimer’s disease (AD). However, whether cataract has an impact on the progression of AD remains unclear. The objective of this research was to determine the relationship between cataracts and AD. A cataract model was established in APP/PS1 [mutant amyloid precursor protein (APP) and a mutant presenilin-1 (PS1) gene] mice via lens puncture. Behavioural assays were used to evaluate cognitive function. Immunohistochemistry, immunofluorescence, and enzyme-linked immunosorbent assays (ELISA) were applied to detect AD-related pathology. Visual signals were markedly obstructed following surgery to induce cataracts, and these mice presented an increased cerebral amyloid-beta (Aβ) load, while no significant alterations in the levels of enzymes associated with Aβ metabolism were detected. In addition, compared with control mice, cataract model mice presented increased astrogliosis and microgliosis, along with elevated levels of proinflammatory factors. Moreover, cataract model mice presented more pronounced cognitive impairments than did control mice. Our study offers experimental confirmation that cataract considerably contributes to the pathogenesis of AD, thereby emphasizing the importance of visual signals in maintaining cognitive well-being.

Selective toxicity and molecular disruption induced by acetamiprid in the predator, Cyrtorhinus lividipennis Reuter (Hemiptera: Miridae) - Naved Ahmad Ansari; Joko Pilianto; Mohd Amir; Abid Ali Soomro; Amr Abou El-Ela; Samar Mahmood; Saleem Javed; Wenwu Zhou; Zeng-Rong Zhu (Science of The Total Environment, 2026)

Performance of blood biomarkers in internal jugular vein for Alzheimer’s disease pathologies: the Delta Method study - Jun Wang; Dong-Yu Fan; Shan Huang; Chang Liu; Pei-Wen Zhao; Nan Wu; Xiao-Lin Gao; Qing-Zhi Wang; Yanli Li; Bai Liu; Yuan-Ye Ma; Rong-Chang Zhao; et al. (Science Bulletin, 2025)

Interaction of secreted protein PgSLP and citrus calmodulin-like protein CsCML27/44 in fruit disease defense - Yao Xu; Ou Chen; Rong Zhu; Rui Huang; Jian Ming; Shixiang Yao; Kaifang Zeng (Postharvest Biology and Technology, 2025)

Consortia of SQR9 mutant strains containing the luxS gene mutation can maintain higher functional stability than the wild type - Jingjing WANG; Lingxue MENG; Ying ZENG; Xinrui ZHU; Chuanyong TANG; Zhihui XU; Hongjun LIU; Rong LI; Qirong SHEN (Pedosphere, 2025)

Development of dCAPS markers for sdhB mutants in fungicide-resistant Botrytis cinerea isolates - Rong Zeng; Ping Gao; Lihui Xu; Ya’nan Yuan; Yufei Han; Jiaxi Tian; Yuhong Wei; Shigang Gao; Zhiwei Song; Pu Zhu; Fuming Dai (Journal of Plant Pathology, 2025)

Glycoside hydrolase PgGal31A inhibits citrus blue mold via modifying cell wall components - Rong Zhu; Ou Chen; Yao Xu; Jian Huang; Huali Wang; Lili Deng; Shixiang Yao; Lanhua Yi; Kaifang Zeng (Postharvest Biology and Technology, 2025)

Identification of Mood Disorders Causal Genes by Integrating the Brain Proteome and Transcriptome - Rong-kun Zhu; Hong-jian Zhou; Jun Shi; Ling Ge; Yi Lin; Wen-hao Yin; Hui Zeng; Xiong-wei Wang (Molecular Neurobiology, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Epigenetic nanoplatform for synergistic immune activation and immunogenicity restoration enhancing cancer radio-immunotherapy - Zhenhu He; Xiaopei Peng; Jiong Li; Yaning Zhu; Xuan Zhang; Junhong Duan; Jing Ni; Mengtian Ma; Juan Wang; Zhenguo Liu; Bin Feng; Wenbin Zeng; et al. (Chemical Engineering Journal, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Debaryomyces nepalensis enhances suberin deposition in citrus fruit wound by facilitating the synthesis of cinnamic acid and its derivatives - Jian Huang; Qi Chen; Ou Chen; Xiaoquan Gao; Rong Zhu; Rui Huang; Shixiang Yao; Lanhua Yi; Kaifang Zeng (Postharvest Biology and Technology, 2025)

Preparation and performance evaluation of an efficient microbial dust suppressant for dust control in disturbed areas of blast piles in open-pit coal mines - Jie Chen; Haoran Wang; Yi He; Rong Liu; Chuanhui Zeng; Kunyu Yan; Junpeng Zhu (Journal of Environmental Management, 2025)

Pollution status and assessment of seven heavy metals in the seawater and sediments of Hangzhou Bay, China - Rong Zhu; Yan-Yan Zeng; Li-Min Liu; Lu Yin; Kai-Ping Xu; Wei-Feng Chen; Shang-Chun Li; Xiao-Feng Zhou (Marine Pollution Bulletin, 2024)

Transcription factor CcbHLH66 regulates mandarin fruit coloration via modulating the expression of chlorophyll degradation related genes CcRCCR and CcNYC - Huali Wang; Qian Liu; Shufang Deng; Jialin Chen; Jin Han; Rong Zhu; Kaifang Zeng; Lili Deng (Postharvest Biology and Technology, 2024)

Effects of weather parameters on the population dynamics of Megalurothrips usitatus in cowpea fields in Sanya, China - Yunchuan He; Jiamei Geng; Yang Gao; Qiulin Chen; Ying Zhou; Zeng-Rong Zhu (International Journal of Tropical Insect Science, 2024)

Ecotoxicological insights into the effects of triflumezopyrim on P. fuscipes fitness, detoxification pathways, and gene expression - Muhammad Musa Khan; Yuanzheng You; Dylan O'Neill Rothenberg; Pankaj Bhatt; Shah Fahad; Ying Zhou; Zeng-Rong Zhu (Chemosphere, 2024)

OsHRZ1 negatively regulates rice resistant to Magnaporthe oryzae infection by targeting OsVOZ2 - Jia-ying Sun; Zeng-ran Zhou; Yu-qi Wang; Dong-yu Zhu; Dian-rong Ma (Transgenic Research, 2024)

Constructing phonon transport bridges via low-temperature sintering in Diamond@Ag/EP composite to achieve efficient 3D networks structure - Zeyu Zheng; XiaoXin Lu; Liang Xu; Yang Liu; Jianhui Zeng; Hebin Zhang; Jialin Wen; Pengli Zhu; Rong Sun; Weijing Wu (Chemical Engineering Journal, 2024)

The romantic history of signaling pathway discovery in cell death: an updated review - Lei-Yun Wang; Xing-Jian Liu; Qiu-Qi Li; Ying Zhu; Hui-Li Ren; Jia-Nan Song; Jun Zeng; Jie Mei; Hui-Xiang Tian; Ding-Chao Rong; Shao-Hui Zhang (Molecular and Cellular Biochemistry, 2024)

Phosphoric acid pre-swelling strategy constructing acid-doped fluoropoly(aryl pyridinium) membranes to enable high-performance vanadium flow batteries - Tao Ban; Zihui Wang; Yinfei Wang; Yifei Xu; Zhanpeng Jiang; Rong Zeng; Xiuling Zhu (Chemical Engineering Journal, 2024)

Pichia galeiformis-secreted protein PgSLP increases citrus fruit disease resistance by activating amino acid metabolism - Yao Xu; Ou Chen; Rong Zhu; Wenjun Wang; Lili Deng; Shixiang Yao; Kaifang Zeng (Postharvest Biology and Technology, 2024)

Engineered hydrochar from waste reed straw for peroxymonosulfate activation to degrade quinclorac and improve solanaceae plants growth - Chunxia Ding; Can Ye; Wei Zhu; Guangyong Zeng; Xuemei Yao; Yu Ouyang; Jie Rong; Yaping Tao; Xiangying Liu; Yaocheng Deng (Journal of Environmental Management, 2023)

Genome-wide discovery of Pichia galeiformis-secreted proteins and their induction of green mold resistance in citrus fruit - Ou Chen; Rong Zhu; Yao Xu; Shixiang Yao; Lanhua Yi; Kaifang Zeng (Postharvest Biology and Technology, 2023)

Interaction of metabolism-related pathway gene variants with bisphenol A exposure on serum lipid profiles - Heng He; Fuwei Zhang; Shuang Zhou; Shanshan Zhang; Lu Wang; Jiaoyuan Li; Qiang Zeng; Ying Zhu; Jianbo Tian; Jiang Chang; Liming Cheng; Qing Lu; et al. (Environmental Toxicology and Pharmacology, 2023)

A chitin synthase mutation confers widespread resistance to buprofezin, a chitin synthesis inhibitor, in the brown planthopper, Nilaparvata lugens - Bin Zeng; Fu-Rong Chen; Ya-Ting Liu; Di Guo; Yi-Jie Zhang; Ze-Rui Feng; Li-Xiang Wang; John Vontas; Shun-Fan Wu; Kun Yan Zhu; Cong-Fen Gao (Journal of Pest Science, 2023)

Exposure–response relationship between temperature, relative humidity, and varicella: a multicity study in South China - Yihan Li; Jialing Li; Zhihua Zhu; Weilin Zeng; Qi Zhu; Zuhua Rong; Jianxiong Hu; Xing Li; Guanhao He; Jianguo Zhao; Lihua Yin; Yi Quan; et al. (Environmental Science and Pollution Research, 2023)

Naturally-Occurring Antibodies Against Bim are Decreased in Alzheimer’s Disease and Attenuate AD-type Pathology in a Mouse Model - Jie-Ming Jian; Dong-Yu Fan; Ding-Yuan Tian; Yuan Cheng; Pu-Yang Sun; Cheng-Rong Tan; Gui-Hua Zeng; Chen-Yang He; Ye-Ran Wang; Jie Zhu; Xiu-Qing Yao; Yan-Jiang Wang; et al. (Neuroscience Bulletin, 2022)

Functional characterization of tyrosine decarboxylase genes that contribute to acteoside biosynthesis in Rehmannia glutinosa - Yan Hui Yang; Mu Rong Yang; Jian Yu Zhu; Ke Wei Dong; Yan Jie Yi; Rui Fang Li; Lei Zeng; Chang Fu Zhang (Planta, 2022)

Consequences of elevated temperature on the biology, predation, and competitiveness of two mirid predators in the rice ecosystem - Yueliang Bai; Md. Khairul Quais; Wenwu Zhou; Zeng-Rong Zhu (Journal of Pest Science, 2022)

Circular RNA circ_Cabin1 promotes DNA damage in multiple mouse organs via inhibition of non-homologous end-joining repair upon PM2.5 exposure - Huixian Zeng; Meizhen Li; Qiuhan Hua; Yufei Liu; Yueting Shao; Qinqin Diao; Yihui Ling; Han Zhang; Miaoyun Qiu; Jialu Zhu; Xun Li; Rong Zhang; et al. (Archives of Toxicology, 2021)

Model test of the stability degradation of a prestressed anchored rock slope system in a corrosive environment - Cong Li; Rong-tang Zhang; Jie-bing Zhu; Zhi-jun Liu; Bo Lu; Bin Wang; Yu-zhou Jiang; Jie-sheng Liu; Ping Zeng (Journal of Mountain Science, 2020)

An update of the Worldwide Integrated Assessment (WIA) on systemic pesticides. Part 4: Alternatives in major cropping systems - Andrea Veres; Kris A. G. Wyckhuys; Jozsef Kiss; Ferenc Tóth; Giovanni Burgio; Xavier Pons; Carlos Avilla; Stefan Vidal; Jaka Razinger; Renata Bazok; Ewa Matyjaszczyk; Ivan Milosavljević; et al. (Environmental Science and Pollution Research, 2020)
We present a synthetic review and expert consultation that assesses the actual risks posed by arthropod pests in four major crops, identifies targets for integrated pest management (IPM) in terms of cultivated land needing pest control and gauges the implementation “readiness” of non-chemical alternatives. Our assessment focuses on the world’s primary target pests for neonicotinoid-based management: western corn rootworm (WCR, Diabrotica virgifera virgifera ) in maize; wireworms ( Agriotes spp.) in maize and winter wheat; bird cherry-oat aphid ( Rhopalosiphum padi ) in winter wheat; brown planthopper (BPH, Nilaparvata lugens ) in rice; cotton aphid ( Aphis gossypii ) and silver-leaf whitefly (SLW, Bemisia tabaci ) in cotton. First, we queried scientific literature databases and consulted experts from different countries in Europe, North America, and Asia about available IPM tools for each crop-pest system. Next, using an online survey, we quantitatively assessed the economic relevance of target pests by compiling country-level records of crop damage, yield impacts, extent of insecticide usage, and “readiness” status of various pest management alternatives (i.e., research, plot-scale validation, grower-uptake). Biological control received considerable scientific attention, while agronomic strategies (e.g., crop rotation), insurance schemes, decision support systems (DSS), and innovative pesticide application modes were listed as key alternatives. Our study identifies opportunities to advance applied research, IPM technology validation, and grower education to halt or drastically reduce our over-reliance on systemic insecticides globally.

EEG-based mild depression recognition using convolutional neural network - Xiaowei Li; Rong La; Ying Wang; Junhong Niu; Shuai Zeng; Shuting Sun; Jing Zhu (Medical & Biological Engineering & Computing, 2019)

Hyperspectral discrimination of foliar biotic damages in rice using principal component analysis and probabilistic neural network - Zhan-Yu Liu; Jia-Guo Qi; Nan-Nan Wang; Zeng-Rong Zhu; Ju Luo; Li-Juan Liu; Jian Tang; Jia-An Cheng (Precision Agriculture, 2018)

Asymmetric evolution of El Niño and La Niña: the recharge/discharge processes and role of the off-equatorial sea surface height anomaly - Zeng-Zhen Hu; Arun Kumar; Bohua Huang; Jieshun Zhu; Rong-Hua Zhang; Fei-Fei Jin (Climate Dynamics, 2017)

A Volumetric and Functional Connectivity MRI Study of Brain Arginine-Vasopressin Pathways in Autistic Children - Xiao-Jing Shou; Xin-Jie Xu; Xiang-Zhu Zeng; Ying Liu; Hui-Shu Yuan; Yan Xing; Mei-Xiang Jia; Qing-Yun Wei; Song-Ping Han; Rong Zhang; Ji-Sheng Han (Neuroscience Bulletin, 2017)

De novo analysis of the Tenebrio molitor (Coleoptera: Tenebrionidae) transcriptome and identification of putative glutathione S-transferase genes - Su Liu; Xiao-Xiao Shi; Yan-Dong Jiang; Zi-Jie Zhu; Ping Qian; Min-Jing Zhang; Hang Yu; Qing-Zi Zhu; Zhong-Jun Gong; Zeng-Rong Zhu (Applied Entomology and Zoology, 2015)

Identification of a Novel Mutation in the Presenilin 1 Gene in a Chinese Alzheimer’s Disease Family - Bo Deng; Yan Lian; Xin Wang; Fan Zeng; Bin Jiao; Ye-Ran Wang; Chun-Rong Liang; Yu-Hui Liu; Xian-Le Bu; Xiu-Qing Yao; Chi Zhu; Lu Shen; et al. (Neurotoxicity Research, 2014)

Characterization of the expression profile of calpain-3 (CAPN3) gene in chicken - Zeng-Rong Zhang; Qing Zhu; Yong-Gang Yao; Xiao-Song Jiang; Hua-Rui Du; Yi-Ping Liu (Molecular Biology Reports, 2012)

Characterization of the expression profiles of calpastatin (CAST) gene in chicken - Zeng-Rong Zhang; Xiao-Song Jiang; Hua-Rui Du; Qing Zhu; Xiao-Cheng Li; Chao-Wu Yang; Yi-Ping Liu (Molecular Biology Reports, 2012)

Endophytic fungus Cladosporium cladosporioides LF70 from Huperzia serrata produces Huperzine A - Zhi Bin Zhang; Qing Gui Zeng; Ri Ming Yan; Ya Wang; Zheng Rong Zou; Du Zhu (World Journal of Microbiology and Biotechnology, 2011)

Molecular cloning and sequence analysis of the sisomicin biosynthetic gene cluster from Micromonospora inyoensis - Wen-Rong Hong; Mei Ge; Zhi-Hong Zeng; Li Zhu; Min-Yu Luo; Lei Shao; Dai-Jie Chen (Biotechnology Letters, 2009)

Morphology and genome of Euproctis pseudoconspersa nucleopolyhedrovirus - Xu-Dong Tang; Qiang Xiao; Xiu-Cui Ma; Zeng-Rong Zhu; Chuan-Xi Zhang (Virus Genes, 2009)

Molecular cloning and sequence analysis of the sisomicin biosynthetic gene cluster from Micromonospora inyoensis - Wun-Rong Hong; Mei Ge; Zhi-Hong Zeng; Li Zhu; Min-Yu Luo; Lei Shao; Dai-Jie Chen (Biotechnology Letters, 2009)

Increased expression of hLRH-1 in human gastric cancer and its implication in tumorigenesis - Shui-Liang Wang; De-Zhu Zheng; Feng-Hua Lan; Xiao-Jun Deng; Jian Zeng; Cheng-Jin Li; Rong Wang; Zhong-Yong Zhu (Molecular and Cellular Biochemistry, 2008)

Complex influence of rice variety, fertilization timing, and insecticide on population dynamics of Sogatella furcifera (Horvath) , Nilaparvata lugens (Stl) (Homoptera: Delphacidae) and their natural enemies in rice in Hangzhou, China - Zeng-Rong Zhu; Jiaan Cheng; Ming-Xing Jiang; Xiao-Xi Zhang (Journal of Pest Science, 2004)